Hardware Development and Analysis of Vehicle’s Driver Awareness during Braking Event - Nor Walid, Nurul Dayana Balqis; Sulaiman, Syabillah; Azizul, Muhammad Asri; Mustaffa, Norrizal (Journal of Advanced Industrial Technology and Application, 2022)
Safety is the most important factor in both manufacturing vehicles as well as when driving and riding. Passive and active system are the two main categories of safety system, thus, this project focus on the active system which where the brake system is located to avoid any collision in critical situation especially rear-end collision. The main objective of this project is to study the driver’s braking response in car-following situations. Data Acquisition System using Arduino IDE was developed, which lead to analyzing the driver’s brake response during emergency braking event. Two types of vehicles were used, which are the Yamaha 135LC motorcycle and Perodua Myvi 1.3L, which also known as Test Vehicle 1 (TV 1) and Test Vehicle 2 (TV 2) respectively. The Data Acquisition System (DAQ) system to record the brake response time of driver in TV 2 as the driver reacts to the activation of brake lights of TV 1 by using the ESP8266 (Wi-Fi controller) was developed. The DAQ installed in TV 1 was connected wirelessly to the DAQ installed in TV 2. Arduino IDE software was used as a medium to transfer data from the push-button sensor to the laptop with the assist of ESP8266 board as the microcontroller, that is connected to the push-button sensor. Two brake lights were tested, which were standard brake lights and flashing brake lights. Each brake lights were tested with three different speeds, which are 20, 30 and 40 km/h. Experiment was carried out at night, where TV 1 braked at any straight road around the campus. Generally, the results indicates that for each speed tested for both brake lights, the brake response time increases as speed increases. The overall results suggested that flashing brake lights has a significantly shorter brake response time with average of 145, 144, 173 ms for 20, 30 and 40 km/h respectively. With average percentage of 12.8% faster brake response time